2014
DOI: 10.1111/jsm.12418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CNS Neurons Innervating the Levator Ani and Ventral Bulbospongiosus Muscles in Male Rats

Abstract: Introduction The pelvic striated muscles play an important role in mediating erections and ejaculation, and together these muscles compose a tightly coordinated neuromuscular system that is androgen sensitive and sexually dimorphic. Aim To identify spinal and brains neurons involved in the control of the levator ani (LA) and bulbospongiosus (BS) in the male adult and preadolescent rat. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 93 publications
(129 reference statements)
2
17
0
Order By: Relevance
“…Interestingly, different pelvic organs may be innervated by a convergent pathways [85]. Coordinate sexual reflexes may also need integrated central regulation pathways in spinal cord and brain [86]. VIP may be relevant to the neural control of micturition [87,88], constipation [89], erectile function [23,79,90].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, different pelvic organs may be innervated by a convergent pathways [85]. Coordinate sexual reflexes may also need integrated central regulation pathways in spinal cord and brain [86]. VIP may be relevant to the neural control of micturition [87,88], constipation [89], erectile function [23,79,90].…”
Section: Discussionmentioning
confidence: 99%
“…Using HVEM, we further demonstrated that the terminals of GRP neurons may form 3-D multiple synapses with the dendrites of SPN neurons revealed by a double immunohistochemical study (Oti et al, 2012). Using a viral trans-synaptic retrograde tracing technique, Dobberfuhl et al (2014) recently reported that after the pseudorabies virus (PRV) injection into the levator ani muscle, about a half of PRV-positive neurons in the medial gray at the upper lumbar spinal cord level expressed GRP. Interestingly, very few PRV-labeled spinal interneurons were found in the medial region of the upper lumbar spinal cord in preadolescent pups.…”
Section: Interaction Of the Grp System With Both The Autonomic And Somentioning
confidence: 99%
“…10,11,13,18 The SAN provides autonomic preganglionic fibers to the genitalia. 21,22 Spinal GRP-positive axons have also been shown to make direct synaptic contacts with somatic motor neurons of the spinal nucleus of bulbocavernosus (SNB) located in the sacral spinal cord in male rats, 33,34 and GRP-sensitive receptors are expressed by rat SNB motor neurons. 10,25 The SNB in rats, which innervates the striated perineal muscles attached to the base of the penis, 9,35-37 is homologous with the human Onuf's nucleus, a sexually dimorphic nucleus located in the motor neuron pools of the sacral spinal cord that has an important role in the micturition and defecatory as well as in rhythmic contractions of perineal muscles during orgasm.…”
Section: Discussionmentioning
confidence: 99%